Pengaruh Validity dan Reliability Terhadap Kualitas Delivery PT. Hanoman Sakti Pratama - Fatrodin Fatrodin (Sekolah Tinggi Maritim Yogyakarta, 2020)
Fierce competition lead to bush freight forwarding services are needed in the business. Study aim is to measure the quality of delivery of PT. Hanoman Sakti Pratama forwarding on customer's perception satisfaction-based. The results: (1) Validity-reliability-delivery quality shows that the stream line flow, the correlation coefficient of validity to reliability is smaller than the validity of delivery quality; (2) Delivery reliability is affected by goods when delivered on time, no additional costs, and does not cause claims due to damaged goods during handling delivery; (3) Delivery quality effectively on consumers is influenced by reliability of delivery with friendly handling, and after delivery service.